Améliorer les instances d’autorégulation de la publicité sexiste - Benoit Cordelier; Yanick Farmer; Mylène Fauvel (Communication)
This research brief provides a broad-brush description of the results of a project whose objectives were: 1) to compare different countries’ self-regulated programs governing sexist advertising with a view to recommending the most appropriate practices for implementation in Quebec's advertising industry; 2) to do a documentary analysis and carry out a survey among a sample of advertisers, advertising agencies and consumer advocacy associations to gauge their knowledge of Quebec's self-regulated programs. Two data gathering tools were used: documentary analysis and online survey.